DO VALUE ORIENTATIONS PREDICT CIVIC ENGAGEMENT OF A PERSON? - Grigoryan, N. A. (Արդի հոգեբանություն, 2018)
The article aims at investigating the relationship between value orientations and person’s readiness to engage in civic activism. The article discusses the influence of value orientations on a person’s readiness for engagement in three civic situations. Data analysis of the study show that value orientations, in particular openness to change, self-enhancement and self-transcendent values are positive predictors for civic engagement and the conservative values are negative predictors for two situations discussed in the article.